Faktor Pendorong Prestasi Belajar Peserta Didik SD Makassar - Mario Mario (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
The study was used to see the driving factors of learning achievement, using functional structural theory and motivation theory. This research uses a qualitative approach that aims to obtain a complete picture of something according to the human view studied. The data collection techniques we carried out included observation, interviews with 8 students and homeroom teachers from grade 5. Based on the research that has been done, we can draw conclusions about the driving factors for the learning achievement of grade 5 students at SD Inpres Tello Baru III Makassar. The driving factors for learning achievement consist of internal factors and external factors. There are 4 internal factors, namely physical health, psychological, motivation, and emotional intelligence. The psychological factors are further divided into intelligence, talents and interests. While visible external factors can be seen from the family environment and also the school environment. The two factors are further divided, where family environment factors are divided into 3, namely parental attention, home atmosphere, and family economic conditions. School environmental factors are divided into 2, namely teachers and learning tools and media.